Influencing factors tax aggressiveness: liquidity, leverage, and profitability - Hamonangan, Stanley (Universitas Wiralodra, 2023)
Previous and related research is very important in an ongoing process of writing scientific articles. The point is to find comparisons and inspiration for writers. Another thing to strengthen the theory and phenomenon of the relationship and influence between the specified variables. This article reviews the factors that influence tax aggressiveness on liquidity, leverage and profitability. The approach used is a literature review on tax accounting. The purpose of writing this article is to build a hypothesis on the influence between variables to be used in further research. The results of this literature review article are that liquidity has an effect on tax aggressiveness, leverage has an effect on tax aggressiveness and profitability has an effect on tax aggressiveness.